Theoretical validation of the step potential electrochemical spectroscopy (SPECS) and multiple potential step chronoamperometry (MUSCA) methods for pseudocapacitive electrodes. (20th October 2019) - Munteshari, Obaidallah; Zhou, Yucheng; Mei, Bing-Ang; Pilon, Laurent
Abstract: This study theoretically and rigorously validates the use of the recently proposed step potential electrochemical spectroscopy (SPECS) and multiple potential step chronoamperometry (MUSCA) methods and their fitting analysis for determining the respective contributions of electrical double layer (EDL) and faradaic reactions to charge storage in pseudocapacitive electrodes. The continuum modified Poisson-Nernst-Planck model coupled with the Frumkin-Butler-Volmer theory were used for simulating interfacial, transport, and electrochemical phenomena in pseudocapacitive electrodes. The model accounted for (i) electron transport in the electrode, (ii) reversible redox reactions, (iii) ion electrodiffusion in binary and symmetric electrolytes, (iv) ion intercalation into the pseudocapacitive electrode, and (v) steric repulsion due to finite ion size. First, typical experimental measurements obtained from the SPECS method were reproduced numerically for a planar pseudocapacitive electrode. The EDL and faradaic currents retrieved from the SPECS fitting procedure were found to be in excellent agreement with those defined from first principles and computed numerically. Here, the faradaic current was modeled in the SPECS method as a diffusion process accounting for interfacial charge transfer kinetics and IR drop. The resistance obtained by SPECS matched the internal resistance obtained from electrochemical impedance spectroscopy. Similarly, the EDL capacitance retrieved by SPECS corresponded to the differential capacitance obtained from cyclic voltammetry (CV). Finally, the CV curves were successfully corrected for ohmic polarization effect using the MUSCA method. Then, the capacitive and diffusive currents retrieved from the electrochemical analysis of CV curves corrected by the MUSCA method were in good agreement with the EDL and faradaic currents reconstructed from the MUSCA method. Graphical abstract: Image 1 Highlights: The SPECS and MUSCA methods were validated using continuum modeling. SPECS successfully distinguished between EDL and faradaic currents. SPECS can retrieve the internal resistance and differential capacitance due to EDL. SPECS can identify the EDL and faradaic regimes and agrees with b-value analysis. k1, k2 analysis can retrieved EDL and faradaic currents from CV curves produced by MUSCA.